NLP Web Services for Slovene and English: Morphosyntactic Tagging, Lemmatisation and Definition Extraction - Pollak, Senja; Trdin, Nejc; Vavpetič, Anže; Erjavec, Tomaž (Informatica)
NLP Web Services for Slovene and English: Morphosyntactic Tagging, Lemmatisation and Definition Extraction